2022
DOI: 10.1007/s12028-022-01571-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute Headache Management for Patients with Subarachnoid Hemorrhage: An International Survey of Health Care Providers

Abstract: Background: Severe headaches are common after subarachnoid hemorrhage (SAH). Guidelines recommend treatment with acetaminophen and opioids, but patient data show that headaches often persist despite multimodal treatment approaches. Considering an overall slim body of data for a common complaint affecting SAH patients during their intensive care stay, we set out to assess practice patterns in headache management among clinicians who treat patients with SAH.Methods: We conducted an international cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Despite these improvements, and a high prevalence of HASH, research in this area is lacking including, phenotypic HASH data, efficacious treatment options and treatment guidelines for providers. In the first cross-sectional worldwide study on HASH, Maciel et al reported that HASH is recognized as a major clinical concern in 87% of providers, opioids are perceived as the most effective analgesic modality, and nearly half the providers prescribe opioids at discharge ( 9 ). This is problematic, given the drawbacks of opioid usage in the acute phase of injury following aSAH, as well as longer term, given the high potential for addiction and contribution to the ongoing opioid epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite these improvements, and a high prevalence of HASH, research in this area is lacking including, phenotypic HASH data, efficacious treatment options and treatment guidelines for providers. In the first cross-sectional worldwide study on HASH, Maciel et al reported that HASH is recognized as a major clinical concern in 87% of providers, opioids are perceived as the most effective analgesic modality, and nearly half the providers prescribe opioids at discharge ( 9 ). This is problematic, given the drawbacks of opioid usage in the acute phase of injury following aSAH, as well as longer term, given the high potential for addiction and contribution to the ongoing opioid epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CGRP-modulating therapies in acute conditions such as traumatic brain injury and SAH continues to be explored ( 29 , 30 ). Data on the effectiveness and safety of NSAIDs are limited in HASH, with over 50% of providers stating they rarely or never used NSAIDS in this setting ( 9 ), likely due to perceived risk of worsening bleeding. Systemic dexamethasone is often reserved for refractory cases due to systemic adverse effects of hyperglycemia, reduced sleep, and possible interference with wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that 70% of opioid-naive patients with below-average opioid use during their hospital stay and low pain scores on discharge still received an opioid prescription upon discharge [ 21 ]. Since there is no institutional protocol with respect to the prescribing OME, the dose prescribed may very well be influenced by the subjective opinion of the treating physician, a finding observed in the neurocritical care setting [ 22 ]. Our study finds that opioid use is common in the postoperative period [ 23 ].…”
Section: Discussionmentioning
confidence: 99%